Anhedonia in endometriosis: An unexplored symptom - Mallorquí, Aida; Martínez-Zamora, María-Angeles; Carmona, Francisco (Frontiers in Psychology, 2022)
Anhedonia is the diminished motivation and sensitivity to pleasurable stimuli. It has been reported to be more prevalent in patients with chronic pain as compared to healthy controls. Endometriosis is a chronic inflammatory systemic disease with a significant psychosocial impact that compromises wellbeing and the day-to-day life of patients. Women with endometriosis show significant psychological distress, even more pervasive when chronic pelvic pain is present. In the current review we will discuss the role of anhedonia in endometriotic chronic pelvic pain. We will also present new lines of research that could lead to more fully clarifying the psychological impact of endometriosis and its detrimental repercussions to quality of life and mental health.